No hiding place for BOB inside myeloma - Stauss, Hans J. (Blood, 2017)
In this issue of Blood, Jahn and colleagues have demonstrated that T-cell receptor (TCR) gene transfer can produce cytotoxic T cells that are capable of eliminating myeloma cells in vivo.(1) The therapeutic TCR can equip human T cells with specificity for octamer binding protein-1 (BOB1), a transcription coactivator that is expressed in normal B cells, multiple myeloma, and B-lineage malignancies, thus providing novel options for immunotherapy of B-cell tumors that do not express CD19 or other surface antigens suitable for targeting with chimeric antigen receptor (CAR)–engineered T cells (see figure).